TRENDS IN THE DEVELOPMENT OF THE REGIONAL SERVICE SYSTEM IN THE CONTEXT OF AN INNOVATIVE ECONOMY: REGIONAL DIFFERENCES AND INTEGRATION OPPORTUNITIES. (Multidisciplinary Journal of Science and Technology, 2025)
In the context of an innovative economy, the development of a regional service system is of paramount importance for improving the quality of life of the population and ensuring the competitiveness of regions. The article analyzes the development trends of the regional service system in the context of digitalization, sustainable development, and interregional integration. Based on the experience of European countries (Germany, Estonia, Poland), successful approaches have been identified that serve to reduce regional differences and strengthen cooperation. System analysis, SWOT analysis, and cluster modeling methods were used to assess the current state and integration potential. The results show that with the introduction of digital platforms and interregional cooperation, the efficiency of the regional service system increases by 35-40%. Based on the best practices of the European Union, recommendations have been developed for the harmonization of regional policy and the development of integration mechanisms.